P3.201 Recent Syphilis Predicts Hepatitis C Virus (HCV) Seroconversion Among HIV-Positive Men Who Have Sex with Men (MSM). (13th July 2013) - Burchell, A N; Manno, M; Gardner, S; Mazzulli, T; Remis, R S; Bayoumi, A; McGee, F; Millson, P; Raboud, J; Rourke, S B
Abstract : Background: There is evidence of sexual HCV transmission among HIV-positive MSM from the UK and Europe. We estimated HCV seroincidence and its risk factors in a North American population of HIV-positive MSM with no known history of injection drug use. Methods: We analysed data from the OHTN Cohort Study, an ongoing cohort of persons in HIV care in Ontario, Canada. Data were obtained from medical charts, interviews, and record linkage with the provincial public health laboratories. We restricted the analysis to 1, 534 MSM who: (1) did not report injection drug use; (2) were under follow-up in 2000–2010; and (3) had 2+ HCV antibody tests, of which the first was negative. Person-time commenced at the later of the HCV-negative result or HIV diagnosis and ended at the first HCV+ or last date of follow-up (median 6.1 person-years (PY) of follow-up; sum 9, 987PY). Results: We observed 51 HCV seroconversions, for an overall incidence of 0.51 per 100PY (CI: 0.39–0.67). Annual incidence varied from 0.16 to 0.89 per 100 PY, with no statistical evidence of a temporal trend. Seroconversion was statistically-significantly associated with acute syphilis infection in the previous 6 months (adjusted hazard ratio = 4.9, CI 1.2–21) and there was a marginally statistically-significant association for men who had not yet initiated antiretroviral treatment (adjusted hazard ratio = 1.9, CI 0.91–4.0). There were no statistically significant effects of age, ethnicity, region, CD4+ cell count or viral load. Conclusion: Sexual behaviour was unmeasured and we cannot exclude the possibility of HCV acquisition via unreported injection drug use. Nevertheless, the strong association with recent syphilis suggests that at least some cases were due to sexual transmission. Future research is needed to establish whether syphilis is a marker for high-risk behaviour or may potentiate sexual HCV transmission among persons with HIV.